Effect of early neonatal vitamin A supplementation on mortality during infancy in Ghana (Neovita): a randomised, double-blind, placebo-controlled trial. Issue 9975 (4th April 2015) - Edmond, Karen M; Newton, Sam; Shannon, Caitlin; O'Leary, Maureen; Hurt, Lisa; Thomas, Gyan; Amenga-Etego, Seeba; Tawiah-Agyemang, Charlotte; Gram, Lu; Hurt, Chris N; Bahl, Rajiv; Owusu-Agyei, Seth; et al.
Summary: Background: Results of randomised controlled trials of newborn (age 1–3 days) vitamin A supplementation have been inconclusive. The WHO is coordinating three large randomised trials in Ghana, India, and Tanzania (Neovita trials). We present the findings of the Neovita trial in Ghana. Methods: This study was a population-based, individually randomised, double-blind, placebo-controlled trial in the Brong Ahafo region of Ghana. The trial participants were infants aged at least 2 h, identified at home or facilities on the day of birth or in the next 2 days, able to feed orally, and likely to stay in the study area for at least 6 months. They were randomly assigned (ratio 1:1) to receive either one oral dose of vitamin A (50 000 IU) or placebo immediately after recruitment. The research team and parents of the infants were masked to treatment assignment. Follow-up home visits were undertaken every 4 weeks, when data were recorded for deaths, facility use, and care seeking. The primary outcome was post-supplementation mortality to 6 months of age. Analysis was by intention to treat. Potential adverse events were recorded at 1 and 3 days after supplementation. This trial is registered with the Australian New Zealand Clinical Trials Registry (ANZCTR)CTRN12610000582055. Findings: We assessed 26 414 livebirths for eligibility between Aug 16, 2010, and Nov 7, 2011. We recruited 22 955 newborn infants, with 11 474 randomly assigned to receive vitamin A and 11 481 to receive placebo. Loss to follow-up was low with vital status at 6 months of age reported for 22 698 (98·9%) infants. We recorded 278 post-supplementation deaths to 6 months of age in the vitamin A group (mortality risk 24·5 in 1000 supplemented infants) and 248 deaths in the placebo group (mortality risk 21·8 per 1000 supplemented infants), relative risk (RR) 1·12 (95% CI 0·95–1·33; p=0·183) and risk difference (RD) 2·66 (95% CI −1·25 to 6·57; p=0·18). Adverse events within 3 days of supplementation did not differ by trial group. 122 infants died in the first 3 days after supplementation; 70 (0·6%) in the vitamin A and 52 (0·5%) in the placebo group (risk ratio [RR] 1·35, 95% CI 0·94–1·93, p=0·102). 53 infants were reported to have a bulging fontanelle; 32 (0·3%) in the vitamin A group and 21 (0·2%) in the placebo group (RR 1·53, 0·88–2·62, p=0·130). Interpretation: The results of this trial do not support inclusion of newborn vitamin A supplementation as a child survival strategy in Ghana. Funding: Bill & Melinda Gates Foundation grant to the WHO.